2008
DOI: 10.1097/scs.0b013e3180f610dd
|View full text |Cite
|
Sign up to set email alerts
|

Rotation and Advancement Flap of the Cheek in the Treatment of Rare Craniofacial Clefts

Abstract: The treatment of Tessier no. 3 and no. 4 clefts is controversial, and little is published because of their rarity. Frequently, many surgeries are necessary for correction of these defects, and in some cases, the outcomes are less than the ideal. Aware of that problem, we developed a procedure based on the Van der Meulen rotation and advancement flap of the cheek that may correct the cleft with 1 simple procedure and also respects the aesthetic units of the face. We report 3 patients presenting cleft no. 3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Other authors have reported an incidence of 9.5 to 34 per 1000 among all cleft cases [1, 2]. The aetiology of the clefts can be explained through a failure in the fusion of the mesoderm during the embryonic process.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors have reported an incidence of 9.5 to 34 per 1000 among all cleft cases [1, 2]. The aetiology of the clefts can be explained through a failure in the fusion of the mesoderm during the embryonic process.…”
mentioning
confidence: 99%
“…These techniques mentioned in the literature for the repair of clefts include the Z-plasty [9], local flaps [1, 10], cheek rotation flap including the lower eyelid [11], rotation and advancement flap of the cheek [2], and the tissue expansion [4, 12] methods. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, due to the width of the coloboma and the subsequent shortness of the lid, we advanced a Mustardè cheek rotation flap with a temporal extension (Van der Meulen, 1985;Mustardé, 1991;Giglio et al, 2008), which included the lid remnant.…”
Section: Discussionmentioning
confidence: 96%
“…For reconstruction, we used the cheek rotation flap that included the eyelid remnant that was dissected, advanced, and sutured to the medial palpebral ligament (Mustardé, 1991;Giglio et al, 2008). A transnasal canthopexy was also performed primarily on each side at the time of the cleft closure.…”
Section: Case Reportmentioning
confidence: 99%